Calcium nutrition nanoagent rescues tomatoes from mosaic virus disease by accelerating calcium transport and activating antiviral immunity - Yan, Shuo; Hu, Qian; Wei, Ying; Jiang, Qinhong; Yin, Meizhen; Dong, Min; Shen, Jie; Du, Xiangge (Frontiers in Plant Science, 2022)
As an essential structural, metabolic and signaling element, calcium shows low remobilization from old to young tissues in plants, restricting the nutrient-use efficiency and control efficacy against mosaic virus disease. Nanotechnology has been applied to prevent/minimize nutrient losses and improve the accessibility of poorly-available nutrients. Herein, the current study applied a star polycation (SPc) to prepare a calcium nutrition nanoagent. The SPc could assemble with calcium glycinate through hydrogen bond and Van der Waals force, forming stable spherical particles with nanoscale size (17.72 nm). Transcriptomic results revealed that the calcium glycinate/SPc complex could activate the expression of many transport-related genes and disease resistance genes in tomatoes, suggesting the enhanced transport and antiviral immunity of SPc-loaded calcium glycinate. Reasonably, the calcium transport was accelerated by 3.17 times into tomato leaves with the help of SPc, and the protective effect of calcium glycinate was remarkably improved to 77.40% and 67.31% toward tomato mosaic virus with the help of SPc after the third and fifth applications. Furthermore, SPc-loaded calcium glycinate could be applied to increase the leaf photosynthetic rate and control the unusual fast growth of tomatoes. The current study is the first success to apply nano-delivery system for enhanced calcium transport and antiviral immunity, which is beneficial for increasing nutrient-use efficiency and shows good prospects for field application.